FAST NEUTRONS INDUCED GENETIC VARIABILITY ON BAMBARA NUT (VIGNA SUBTERRANEAN (L.) VERDC.) - A.E. Esson, M.I. Adebola, (Horticultural Biotechnology Research)
In this study, two accessions of Bambara groundnut were exposed to fast neutrons Americium-Beryllium (AmBe) source with flux of 1.5 ×104 ncm-2 s-1for different hours, and planted in a completely randomized block design (RCBD) with three replications to raise M1 generation. The data recorded were percentage germination, plant height, number of leaves, leaf length, leaf width, days to 50% flowering, number of pods per plant, fresh weight of plants, dry weight of plants, dry weight of pods, weight of seeds and100 seeds weight. There was variation in plant height, number of leaves, leaf length, leaf width, Days to 50% flowering, fresh weight of plants, dry weight of plants, dry weight of pods, weight of seeds and100 seeds weight for Black accession. In the Cream accession, days to 50% flowering, number of pods per plant, fresh weight of plants, dry weight of plants, dry weight of pods, weight of seeds and100 seeds weight were significantly different. Treatment at 16 hours performed best for plant height, leaf length, number of leaves, weight of seed per plant and 100 seed weight in Black accession while Cream performed best at 8 hours exposure time. Fast neutron was observed to improve the performance of Bambara groundnut, thus can be used in breeding programme for Bambara groundnut.